2022
DOI: 10.3389/fpsyt.2022.884529
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup bias in punishing behaviors of adults with autism spectrum disorder

Abstract: Groups are essential elements of society, and humans, by nature, commonly manifest intergroup bias (i.e., behave more positively toward an ingroup member than toward an outgroup member). Despite the growing evidence of various types of altered decision-making in individuals with autism spectrum disorder (ASD), their behavior under the situation involving group membership remains largely unexplored. By modifying a third-party punishment paradigm, we investigated intergroup bias in individuals with ASD and typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…Considering results in the recent autism literature, this is consistent with some studies on the cross-race effect (Wilson et al, 2011;Yi et al, 2016;Yi et al, 2015), although differs from a number of other studies (Hadad et al, 2019;Kang et al, 2020). It is possible that these latter studies involved tasks that autistic people struggled more with, such as judging social norms (Qian et al, 2022) and direct gaze aversion (Uono et al, 2021), making intergroup modulation harder to detect, whilst we were using a task that autistic were capable of, albeit to a lesser extent than non-autistic people (see below).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Considering results in the recent autism literature, this is consistent with some studies on the cross-race effect (Wilson et al, 2011;Yi et al, 2016;Yi et al, 2015), although differs from a number of other studies (Hadad et al, 2019;Kang et al, 2020). It is possible that these latter studies involved tasks that autistic people struggled more with, such as judging social norms (Qian et al, 2022) and direct gaze aversion (Uono et al, 2021), making intergroup modulation harder to detect, whilst we were using a task that autistic were capable of, albeit to a lesser extent than non-autistic people (see below).…”
Section: Discussionsupporting
confidence: 88%
“…While no study has assessed an intergroup bias in smile authenticity judgements in autism, a few recent studies have suggested that intergroup bias is attenuated and even absent in autistic people in studies using definite intergroup boundaries (e.g., nationality) and in nonautistic adults with high autistic traits in studies using minimal group settings. Qian et al (2022) investigated intergroup bias in "third-party punishment" behaviours in autistic adults and found that non-autistic adults penalised outgroup members more harshly than ingroup members by removing money, but this ingroup favouritism was attenuated in autistic adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation